Eleven Theses on Sound and Transcendence - Kane, Brian (Current Musicology, 2013)
How can technê both imitate nature, and thus duplicate the model that nature provides, while simultaneously perfecting or accomplishing what nature cannot achieve? Where would technê have learned its skill at fulfilling nature’s ends (and better than nature itself)? How can technê be both disciple and master of physis? The Peripatetic’s competing views about the relationship of physis and technê cannot be consistently reconciled (with apologies to the apologetic Ancient commentators). If technê comes to the aid of physis, and brings physis to completion, then physis cannot be conceived as a simple plenitude or potentiality without lack. Thus the inability of physis to realize its ends without the aid of technê reveals that the relationship of the two cannot be simple subordination. Rather, the relationship is supplementary.